Mapping Design of The Impact of Covid-19 in Yogyakarta Using SIG - Willy Pratama Cendana; Esi Putri Silmina; Syaiful Rachmat Dana; Firmansyah (Procedia of Engineering and Life Science, 2021)
This study describes how the Covid-19 impact mapping design in the Special Region of Yogyakarta uses the Geographical Information System. The spread of Covid-19, which is getting more massive and is increasing again in D.I Yogyakarta, requires evaluation of implementing government policies. Making it easier for the public to understand the presentation of data and the distribution of Civil-19 in each region in D.I Yogyakarta is important to be updated again because, with clarity and easy access, the public can easily find out the data on the significant distribution of Covid-19 and is supported by valid data. This encourages us to research by utilizing the Geographical Information System to carry out mapping in DI Yogyakarta by presenting it via the website and also an application that is always updated with the latest information related to Covid-19 distribution data in Yogyakarta. From the results of our discussion, it is clear that the presentation of geographic data from D.I Yogyakrta and mapping the areas affected by Covid-19 using GIS will be more profitable because the presentation of the data will be easier to understand by the public, and more updated in real time.